Cavitation-erosion-resistant carburized YSZ-C ceramic material and preparation method thereof
By introducing carbon elements into zirconia ceramics, carburized YSZ-C ceramic materials are formed, which solves the problems of prone to cracking and insufficient mechanical properties of traditional zirconia ceramics at high temperature sintering, significantly improves its hardness and cavitation resistance, and is suitable for High-speed overcurrent components.
Patent Information
- Application Number
- CN202411644763.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-11-18
AI Technical Summary
Traditional zirconia ceramic materials are prone to cracking during high-temperature sintering, and their mechanical properties and cavitation resistance are insufficient, making it difficult to meet the cavitation resistance needs of high-speed overcurrent components.
Using yttrium oxide-stabilized zirconia powder as raw material, carbon elements are added to form carburized YSZ-C ceramic material through ball milling and hot pressing sintering technology, and uniformly penetrates into YSZ using the migration potential energy of carbon atoms to reduce residual stress and brittleness. Improve firing success rate and mechanical properties.
It significantly improves the hardness, toughness and cavitation resistance of YSZ-C ceramic materials, reduces cavitation loss, and makes the surface of the material more hydrophobic, which can more effectively resist the mechanical impact caused by cavitation collapse.
Smart Images

Figure CN119263824A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a cavitation-resistant carburized YSZ-C bulk ceramic material, in particular to a black carburized YSZ-C bulk ceramic with cavitation-resistant effect and a preparation method thereof, belonging to the technical field of structural ceramics and cavitation-resistant ceramic material preparation. Background Art
[0002] The service failure of materials has always been the main factor restricting the upgrading of core technologies in the high-end manufacturing industry. Among them, cavitation damage (or cavitation) in high-speed flow components such as turbine ball valves, turbines, pumps, and propellers is extremely harmful. For example, the core component of hydropower generation, the turbine, causes an annual power generation loss of more than 128 billion degrees due to cavitation damage; the cavitation of propellers greatly affects the stability and reliability of ship navigation; the ball valves in the pipelines of various chemical plants are prone to sealing leakage due to cavitation damage, which brings great uncertainty to the safe production of products. The reason why the cavitation problem is difficult to solve is mainly because under the combined action of shock waves, microjets and instantaneous high temperatures formed by the collapse of cavitation bubbles, traditional materials will almost without exception produce severe fatigue peeling or even breakdown and fracture damage. Therefore, the research and development of new materials with excellent cavitation resistance is of great significance to the upgrading and optimization of various flow components.
[0003] Ceramic materials have been widely used in aerospace, shipbuilding, hydropower, petrochemical, biomedical and other fields due to their high strength, high hardness, high melting point, corrosion resistance and chemical stability. They have become one of the research hotspots of anti-cavitation materials in recent years. At present, common ceramic materials used for anti-cavitation include alumina, silicon nitride, zirconium oxide and glass mica. The literature "Ceram. Int., 1994, 20(3): 201-9." studied the cavitation behavior of various ceramic materials in distilled water and found that they are more resistant to cavitation than metals. Among them, zirconium oxide has multiple toughening mechanisms such as phase transformation toughening, stress microcrack toughening, and ferroelastic toughening. It shows high strength and relatively good toughness among many ceramic materials and is considered to be one of the most promising anti-cavitation ceramic materials. However, pure zirconium oxide is prone to cracking due to the volume change caused by phase transformation during high-temperature sintering. Therefore, it is difficult to obtain a complete ceramic block, and its application is greatly limited. Although the addition of yttria (Y2O3) can stabilize the phase structure of zirconium oxide (ZrO2) during high-temperature sintering to a certain extent and improve the yield rate, the research results of the literature "Wear, 2013, 300(1-2):163–8." found that the mechanical properties, especially the toughness, of yttria-stabilized zirconia (YSZ) ceramics are still biased, and it is still easy to brittlely peel off under the continuous impact of cavitation loads. Therefore, how to further improve the mechanical and cavitation resistance of YSZ has become a difficult problem that needs to be solved in the field of fluid machinery and materials. Summary of the invention
[0004] In response to the problems existing in the above-mentioned background technology, the present invention discloses a cavitation-resistant carburized YSZ-C bulk ceramic material and a preparation method thereof. The material is not only easier to fire, but also has significantly higher comprehensive mechanical properties and changes the contact angle with water. Therefore, the cavitation resistance can be improved by 1 to 2 orders of magnitude compared with traditional YSZ materials, and has obvious advantages as a protective material.
[0005] The technical solution adopted by the present invention is as follows: 1. Preparation of Cavitation-Resistant Carburized YSZ-C Bulk Ceramic Materials 1. Select YSZ (yttria-stabilized zirconia) powder as the raw material, pour it into a ball mill, add deionized water or ethanol 2 to 3 times the mass of YSZ powder into the ball mill as a wet grinding medium, ball mill at 200 to 500 r / min for 20 to 50 hours, then dry and grind to obtain powder.
[0006] The purpose of ball milling is to make the powder and the grinding balls in the jar collide and rub against each other during high-speed motion, so as to crush, grind and disperse the sample.
[0007] Drying is the process of placing the slurry obtained after ball milling into a forced air drying oven for drying; grinding is the process of placing the dried powder into a grinding apparatus such as an agate mortar and grinding it using tools such as an agate grinding rod.
[0008] Preferably, the purity of the YSZ powder is ≥99%, and the particle size ranges from 20 nm to 200 μm.
[0009] Preferably, the content of yttrium oxide in the YSZ powder is 1 mol% to 10 mol%.
[0010] Preferably, the wet grinding medium is deionized water or anhydrous ethanol with a purity of 99%.
[0011] 2. The target powder is pressed into a green body, and the target green body is sequentially loaded into a graphite mold in the order of graphite pad-graphite paper-target green body-graphite paper-target green body-graphite paper for hot pressing and sintering. After sintering, the target product carburized YSZ-C bulk ceramic material is obtained by cooling; vacuum is drawn during the hot pressing and sintering process, and the vacuum degree is ≤10 -1 Pa, the sintering pressure is 10~30 MPa, and the sintering temperature is 1200~1650 ℃.
[0012] Preferably, the carbon content in the graphite paper and the graphite pad is ≥99%.
[0013] The preferred hot pressing sintering process and process parameters are as follows: 1) Heating process: The sample is rapidly heated to 800~1100℃ at a rate of 10~15℃ / min in the furnace and subjected to a sintering pressure of 10~15 MPa; 2) Temperature sintering process: The sample is heated to 1200~1450℃ in the furnace at a rate of 5~15℃ / min and subjected to a sintering pressure of 20~25MPa. The process takes a total of 20~50min. Then, the sample is heated to 1450~1650℃ at a rate of 1~5℃ / min and subjected to a sintering pressure of 25~30MPa. The process lasts for 90~120min. 3) Self-controlled cooling process: cool down to 1100~1400℃ at a rate of 5~10℃ / min, change to 10~15 MPa sintering pressure and keep it for 15~30min, then change to 10MPa sintering pressure and keep it for 20~50min, and after cooling to room temperature, the black cavitation-resistant YSZ-C bulk ceramic material can be obtained.
[0014] The synthesis mechanism of the present invention is as follows: yttria-stabilized zirconia (YSZ) powder is selected as the raw material, wherein the yttria doping content is 1 mol% to 10 mol%. 3+ and Zr 4+ The number of oxygen atoms distributed around the ions is different. 3+ Doping substitution metal Zr 4+ After the lattice position, a large number of oxygen vacancies will be formed in YSZ. Because the radius of the carbon atom is 0.077nm, which is very close to the radius of the oxygen atom of 0.074nm, the present invention uses vacuum hot pressing sintering technology and adopts graphite abrasives, graphite pads and graphite paper to provide an oxygen-free and sufficient carbon atmosphere, which creates favorable conditions for the carbon element to penetrate into YSZ through oxygen vacancies. More importantly, the present invention adopts an ultra-high temperature sintering temperature of 1450~1650℃, which provides a sufficiently high migration potential energy for carbon atoms, helps them overcome the migration energy barrier, and can achieve uniform penetration in the YSZ block. The evenly distributed heterogeneous carbon atoms can not only prevent the excessive growth of YSZ grains, but also reduce residual stress and brittleness, greatly improving the sintering success rate of the block material. In addition, the preferred grinding and sintering processes of the present invention also play a great role in preparing carburized YSZ-C bulk ceramics with excellent structure and performance: if the ball mill fails to reach the predetermined rotation speed and time, it will lead to insufficient powder crushing, and even uneven grain growth of the later sintered samples, affecting their performance; if the sintering temperature is too low, the ceramic block will be sintered loosely, the carburized layer will be shallow, small in amount and uneven in quality; if the insulation time is too long, the grains will grow larger, resulting in poor performance.
[0015] 2. Characterization and properties of cavitation-resistant carburized YSZ-C ceramic block materials 1. Structural characterization Figure 2The YSZ-C bulk ceramic synthesized by the present invention and conventional YSZ bulk ceramics show that YSZ-C is a typical black bulk material, which is completely different from conventional YSZ ceramics which are usually white.
[0016] Figure 3 This is the Raman spectrum of the YSZ-C ceramic material prepared in the present invention. There is an obvious carbon peak in the figure, which is located at about 1360cm -1 The D peak on the left and right is about 1570cm -1 The G peaks on the left and right indicate that carbon can indeed be infiltrated into YSZ in the form of a single substance through the method provided by the present invention.
[0017] Figure 4 This is the SEM image of the thermally etched surface of YSZ-C synthesized in the present invention. Figure 5 This is the EDS spectrum element statistics diagram of YSZ-C. Figure 6 The TEM morphology of the interior of YSZ-C and the corresponding element surface distribution map. It is not difficult to see from these data that the distribution of carbon atoms in the YSZ-C material prepared by the present invention is extremely uniform, and a large amount of carbon exists in the entire material, with a weight percentage of 13.33%, which again shows that carbon atoms have been efficiently infiltrated into YSZ through oxygen vacancies; in addition, the grain size of YSZ-C ceramics is relatively uniform, with a maximum grain size of less than 3μm, indicating that the infiltrated heterogeneous C atoms have a good inhibitory effect on grain growth, which is beneficial to improving the mechanical properties and cavitation resistance of ceramic materials.
[0018] 2. Performance evaluation 2.1 Mechanical properties 1) The hardness of YSZ-C and conventional YSZ ceramic materials was tested using a Vickers microhardness tester. The test conditions were: load 300g, loading duration 5s. The results showed that the microhardness of YSZ-C was 1487.50±29.72 HV 300g , higher than 1395.70±8.89 HV of YSZ 300g .
[0019] 2) Nanoindentation instrument was used to test the nanohardness and elastic modulus of YSZ-C and YSZ ceramic materials. The test conditions were: randomly selected 5 test points, load 10mN, and loading duration 10 s. The results showed that the H IT and H 3 / E* 2 They are 14.56 GPa and 0.111 respectively, which are also significantly higher than 3.15 GPa and 0.003 of YSZ, indicating that the YSZ-C ceramics of the present invention have significantly higher hardness and toughness than traditional YSZ.
[0020] The improvement in toughness of the new YSZ-C ceramic is also reflected in the morphology of its Vickers indentation, such as Figure 7 As shown in the figure, unlike the obvious cracks at the corners of the YSZ indentation, no cracks were observed around the YSZ-C indentation, which once again proves that carburizing can significantly improve the ability of ceramic materials to resist fatigue cracking.
[0021] 2.2 Hydrophilicity The water contact angle of YSZ-C and YSZ ceramic blocks was measured using a DSA100 contact angle meter (KRUSS, Germany). A 5μL water droplet was used for each test, and each sample was measured three times to take the average value. The results showed that the water contact angle of YSZ-C was 70.31°, which was significantly higher than 62° of YSZ, indicating that the ceramic surface of the present invention is more hydrophobic, mainly because the entry of carbon reduces the surface energy of YSZ-C. The hydrophobic and air-philic surface can better prevent cavitation from forming and collapsing around it, and the air film adsorbed on the surface of the material can also effectively alleviate the shock wave and microjet generated by the collapse of cavitation on the ceramic surface, so it is very beneficial to improve the cavitation resistance of the material.
[0022] 2.3 Cavitation performance The cavitation performance test was carried out in deionized water using an ultrasonic cavitation machine. Before the experiment, the polished sample was fixed on the sample stage below the ultrasonic tip, and the sample stage was 12±4mm away from the liquid surface. The upper sample was made of stainless steel with a diameter of 15.9 mm and coaxially installed with the sample to be tested. The distance between the two was about 0.5±0.01 mm. The water bath circulation system kept the temperature of the deionized water within the range of 25±2 ℃, the vibration frequency was 20 kHz, and the amplitude was 50 μm (peak-peak). Before and after the experiment, the sample was ultrasonically cleaned in an ethanol solution for 3 min, and then the mass loss of the sample was measured and recorded using an analytical balance with an accuracy of 0.1 mg.
[0023] The results show that the cavitation incubation period of the YSZ-C ceramic material prepared by the present invention is as long as 9 h, and the cumulative mass loss after cavitation for 10 h is only 0.1 mg, which is 1 to 2 orders of magnitude lower than that of the traditional zirconia ceramics "Ceram. Int., 1994, 20(3): 201-9." and the YSZ ceramics prepared in comparative example 3, showing extremely high anti-cavitation ability.
[0024] Compared with the prior art, the present invention has the following advantages: The present invention utilizes the characteristics that the oxygen vacancies existing in the YSZ material are close to the size of the carbon element, and forms an "oxygen-free carbon-rich" atmosphere environment in a hot pressing furnace by using graphite abrasives, graphite pads and graphite paper and by vacuuming, and then heats to a sufficiently high temperature so that the carbon atoms obtain enough migration energy, thereby smoothly overcoming the energy barrier and uniformly infiltrating all the grains and interfaces on the surface and inside of the YSZ, and obtaining a black YSZ-C ceramic block material with uniform color. This synthesis method has never been reported before, and it is completely newly designed by the inventor based on scientific principles. In addition, the YSZ powder, graphite paper and other materials used in the present invention are simple and common, available on the market, easy to obtain and cheap, and the vacuum hot pressing furnace used is also a common equipment for preparing ceramic block materials. More importantly, the hardness and toughness of the black YSZ-C ceramic material prepared by the present invention are greatly improved compared with YSZ, and it is more hydrophobic and aerophilic, so it can better resist the mechanical impact caused by cavitation collapse in a cavitation environment, and the fatigue peeling is extremely slight, and the cavitation resistance performance is excellent. Therefore, the YSZ-C ceramic material prepared by the present invention is expected to be widely used in the field of fluid machinery. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 The figure is a schematic diagram of the mold and sample loading in the sintering preparation process of the carburized YSZ-C ceramic material of the present invention (① graphite pad, ② graphite paper, ③ target green body, ④ upper pressure rod).
[0026] Figure 2 Digital photos of the YSZ-C bulk ceramics prepared in the present invention and conventional YSZ bulk ceramics.
[0027] Figure 3 This is the Raman spectrum of the carburized YSZ-C ceramic material prepared in the present invention.
[0028] Figure 4 This is a SEM image of the thermally etched surface of the carburized YSZ-C ceramic material prepared in the present invention.
[0029] Figure 5 This is the EDS energy spectrum element distribution diagram of the carburized YSZ-C ceramic material prepared in the present invention.
[0030] Figure 6 TEM morphology and corresponding element surface distribution diagram of the carburized YSZ-C ceramic material prepared in the present invention.
[0031] Figure 7 Vickers indentation SEM images of carburized YSZ-C (a) and conventional YSZ (b) prepared in the present invention. DETAILED DESCRIPTION
[0032] In order to enable those skilled in the art to better understand the technical solution of the present invention, the preparation and performance of the carburized YSZ-C ceramic material of the present invention are further described below in conjunction with implementation examples.
[0033] Example 1 1) 3 mol% yttria-stabilized zirconia (YSZ) powder with a purity of ≥99% and a particle size range of 60-90 μm was selected as the raw material, 100 g was weighed and poured into a ball mill, and 200 g of deionized water was added to the ball mill as a wet grinding medium; the speed of the ball mill was 400 r / min; the ball milling time was 36 h; the slurry obtained above was dried in a blast drying oven at 150 °C for 3 h; finally, the dry powder was ground using an agate mortar to obtain the powder required for sintering.
[0034] 2) Weigh 10 g of the dry target powder obtained in step 1), press it with a manual press at 14 MPa for 10 min to obtain a green body, and then press the obtained target green body Figure 1 The green body, graphite pad and graphite paper were placed in a standard graphite mold with a size of 25 mm × 25 mm × 1500 mm and placed in a vacuum hot press furnace for hot pressing sintering. Hot pressing sintering process conditions: The atmosphere furnace was evacuated to a vacuum reading of <10 -1 Pa; first, the heating process: the sample is rapidly heated to 1100 ℃ at a rate of 10 ℃ / min in the furnace and subjected to a sintering pressure of 12.5 MPa; second, the heating sintering process, the sample is heated to 1400 ℃ at a rate of 10 ℃ / min in the furnace and subjected to a sintering pressure of 20 MPa, the process is a total of 30 min, and then heated to 1600 ℃ at a rate of 5 ℃ / min and subjected to a sintering pressure of 25 MPa, the process lasts for 100 min; 3) followed by a self-controlled cooling process, cooling to 1400 ℃ at a rate of 10 ℃ / min and switching to a sintering pressure of 12.5 MPa for 20 min, then switching to a sintering pressure of 10 MPa for another 30 min. After sintering, the target product, carburized YSZ-C bulk ceramic material, is obtained by cooling the furnace.
[0035] 3) Properties of carburized YSZ-C bulk ceramic material: The appearance color is uniform black, and the microhardness is 1487.50±29.72 HV 300g The cumulative cavitation mass loss after cavitation for 10 h was 0.1 mg, showing excellent anti-cavitation performance.
[0036] Example 2 1) 3 mol% yttria-stabilized zirconia (YSZ) powder with a purity of ≥99% and a particle size range of 60-90 μm was selected as the raw material, 100 g was weighed and poured into a ball mill, and 250 g of anhydrous ethanol was added to the ball mill as a wet grinding medium; the speed of the ball mill was 500 r / min; the ball milling time was 36 h; the slurry obtained above was dried in a blast drying oven at 150 °C for 3 h; finally, the dry powder was ground using an agate mortar to obtain the powder required for sintering.
[0037] 2) Weigh 10 g of the dry target powder obtained in step 1), press it with a manual press at 14 MPa for 10 min to obtain a green body, and then press the obtained target green body Figure 1 The green body, graphite pad and graphite paper were placed in a standard graphite mold with a size of 25 mm × 25 mm × 1500 mm and placed in a vacuum hot press furnace for hot pressing sintering. Hot pressing sintering process conditions: The atmosphere furnace was evacuated to a vacuum reading of <10 -1 Pa; first, the heating process: the sample is rapidly heated to 1100 ℃ at a rate of 10 ℃ / min in the furnace and subjected to a sintering pressure of 12.5 MPa; second, the heating sintering process, the sample is heated to 1400 ℃ at a rate of 10 ℃ / min in the furnace and subjected to a sintering pressure of 20 MPa, the process is a total of 30 minutes, and then the temperature is increased to 1600 ℃ at a rate of 5 ℃ / min and subjected to a sintering pressure of 25 MPa, the process lasts for 100 minutes; 3) followed by a self-controlled cooling process, cooling to 1400 ℃ at a rate of 10 ℃ / min and switching to a sintering pressure of 12.5 MPa for 20 minutes, and then switching to a sintering pressure of 10 MPa for 30 minutes. After sintering, the target product, carburized YSZ-C bulk ceramic material, is obtained by cooling the furnace.
[0038] 3) Properties of carburized YSZ-C bulk ceramic material: The appearance color is uniform black, and the microhardness is 1459.10±26.05 HV 300g The cumulative cavitation mass loss after cavitation for 10 h was 0.1 mg, showing excellent anti-cavitation performance.
[0039] Example 3 1) 3 mol% yttria-stabilized zirconia (YSZ) powder with a purity of ≥99% and a particle size range of 60-90 μm was selected as the raw material, 100 g was weighed and poured into a ball mill, and 250 g of anhydrous was added to the ball mill as a wet grinding medium; the speed of the ball mill was 400 r / min; the ball milling time was 24 h; the slurry obtained above was dried in a blast drying oven at 150 °C for 3 h; finally, the dry powder was ground using an agate mortar to obtain the powder required for sintering.
[0040] 2) Weigh 10 g of the dry target powder obtained in step 1), press it with a manual press at 16 MPa for 15 min to obtain a green body, and then press the obtained target green body Figure 1 The green body, graphite pad and graphite paper were placed in a standard graphite mold with a size of 25 mm × 25 mm × 1500 mm and placed in a vacuum hot press furnace for hot pressing sintering. Hot pressing sintering process conditions: The atmosphere furnace was evacuated to a vacuum reading of <10 -1 Pa; first, the heating process: the sample is rapidly heated to 1100 ℃ at a rate of 10 ℃ / min in the furnace and subjected to a sintering pressure of 12.5 MPa; second, the heating sintering process, the sample is heated to 1400 ℃ at a rate of 10 ℃ / min in the furnace and subjected to a sintering pressure of 20 MPa, the process is a total of 30 min, and then heated to 1600 ℃ at a rate of 5 ℃ / min and subjected to a sintering pressure of 25 MPa, the process lasts for 100 min; 3) followed by a self-controlled cooling process, cooling to 1400 ℃ at a rate of 10 ℃ / min and switching to a sintering pressure of 12.5 MPa for 20 min, then switching to a sintering pressure of 10 MPa for another 30 min. After sintering, the target product, carburized YSZ-C bulk ceramic material, is obtained by cooling the furnace.
[0041] 3) Properties of carburized YSZ-C bulk ceramic material: The appearance color is uniform black, and the microhardness is 1419.50±27.66 HV 300g The cumulative cavitation mass loss after cavitation for 10 h was 0.6 mg, showing excellent anti-cavitation performance.
[0042] Comparative Example 1 1) Select ZrO2 powder with a purity of ≥99% and a particle size range of 80~100 nm as raw material.
[0043] 2) Weigh 10 g of the powder obtained in step 1) and press it with a manual press at 14 MPa for 10 min to obtain a green body. Figure 1The green body, graphite pad and graphite paper were placed in a standard graphite mold with a size of 25 mm × 25 mm × 1500 mm and placed in a vacuum hot press furnace for hot pressing sintering. Hot pressing sintering process conditions: The atmosphere furnace was evacuated to a vacuum reading of <10 -1 Pa; first, the heating process: the sample is rapidly heated to 1100 ℃ at a rate of 10 ℃ / min in the furnace and subjected to a sintering pressure of 12.5 MPa; second, the heating sintering process, the sample is heated to 1400 ℃ at a rate of 10 ℃ / min in the furnace and subjected to a sintering pressure of 20 MPa, the process is a total of 30 minutes, and then the temperature is raised to 1600 ℃ at a rate of 5 ℃ / min and subjected to a sintering pressure of 25 MPa, the process lasts for 100 minutes; 3) followed by a self-controlled cooling process, cooling to 1400 ℃ at a rate of 10 ℃ / min and switching to a sintering pressure of 12.5 MPa for 20 minutes, and then switching to a sintering pressure of 10 MPa for 30 minutes. After sintering, the ZrO2 bulk ceramic material is obtained by cooling the furnace.
[0044] 3) Performance of ZrO2 bulk ceramic material: The appearance color is a white ceramic block, which is very brittle and easy to crack, so it is impossible to carry out further experimental tests such as mechanical properties and cavitation properties. Since pure ZrO2 has no oxygen vacancies, carbon cannot penetrate at high temperatures, so uniformly carburized black ZrO2-C material cannot be obtained. This shows that even if the sintering temperature and carburizing atmosphere conditions are exactly the same as those in the embodiment, as long as the type of raw materials is not within the range specified in the present invention, it is impossible to obtain a carburized ceramic material with good cavitation resistance.
[0045] Comparative Example 2 1) 3 mol% yttria-stabilized zirconia (YSZ) powder with a purity of ≥99% and a particle size range of 60-90 μm was selected as the raw material, 100 g was weighed and poured into a ball mill, and 200 g of deionized water was added to the ball mill as a wet grinding medium; the speed of the ball mill was 400 r / min; the ball milling time was 36 h; the slurry obtained above was dried in a blast drying oven at 150 °C for 3 h; finally, the dry powder was ground using an agate mortar to obtain the powder required for sintering.
[0046] 2) Weigh 10 g of the dry target powder obtained in step 1), press it with a manual press at 14 MPa for 10 min to obtain a green body, and then load the obtained target green body in the order of molybdenum pad-target green body-molybdenum pad-target green body, and then put it into a standard graphite mold with a size of 25 mm×25 mm×1500 mm and molybdenum sheets on all sides, and put it into a vacuum hot pressing furnace for hot pressing sintering. Hot pressing sintering process conditions: vacuum the atmosphere furnace to make the vacuum reading value <10-1 Pa; first, the heating process: the sample is rapidly heated to 1100 ℃ at a rate of 10 ℃ / min in the furnace and subjected to a sintering pressure of 12.5 MPa; second, the heating sintering process, the sample is heated to 1400 ℃ at a rate of 10 ℃ / min in the furnace and subjected to a sintering pressure of 20 MPa, the process is a total of 30 min, and then heated to 1600 ℃ at a rate of 5 ℃ / min and subjected to a sintering pressure of 25 MPa, the process lasts for 100 min; 3) followed by a self-controlled cooling process, cooling to 1400 ℃ at a rate of 10 ℃ / min and switching to a sintering pressure of 12.5 MPa for 20 min, then switching to a sintering pressure of 10 MPa for another 30 min. After sintering, the YSZ bulk ceramic material is obtained by cooling the furnace.
[0047] 3) Performance of YSZ bulk ceramic material: The appearance color is extremely uneven light gray ceramic block, and the block is broken due to too many cracks, so it is impossible to carry out further experimental tests such as mechanical properties and cavitation performance. Since no graphite pads and graphite paper are used, there is a lack of sufficient carbon atmosphere during the high-temperature sintering process. Therefore, even if there are oxygen vacancies in YSZ and the sintering temperature is high enough, carbon cannot penetrate efficiently, so uniformly carburized black YSZ-C material cannot be obtained. This shows that even if the type of raw materials and the sintering process are exactly the same as in the embodiment, as long as the carburizing atmosphere conditions are not within the range specified in the present invention, a carburized ceramic material with good cavitation resistance cannot be obtained.
[0048] Comparative Example 3 1) Select 7 mol% yttria-stabilized zirconia (YSZ) powder with a purity of ≥99% and a particle size range of 80~100 nm as the raw material.
[0049] 2) Weigh 10 g of the powder obtained in step 1) and press it with a manual press at 14 MPa for 10 min to obtain a green body. Figure 1 The green body, graphite pad and graphite paper were placed in a standard graphite mold with a size of 25 mm × 25 mm × 1500 mm and placed in a vacuum hot press furnace for hot pressing sintering. Hot pressing sintering process conditions: The atmosphere furnace was evacuated to a vacuum reading of <10 -1Pa; first, the heating process: the sample is rapidly heated to 400 ° C at a rate of 10 ° C / min in the furnace and subjected to a sintering pressure of 12.5 MPa, then the sample is heated to 1100 ° C at a rate of 10 ° C / min in the furnace and subjected to a sintering pressure of 20 MPa, the process lasts for 110 min, followed by the temperature-raising sintering process, the sample is heated to 1400 ° C at a rate of 10 ° C / min in the furnace and subjected to a sintering pressure of 25 MPa, the process lasts for 150 min. After sintering, the YSZ bulk ceramic material is obtained by cooling the furnace.
[0050] 3) Properties of YSZ bulk ceramic material: The appearance color is uneven gray, and the microhardness is 1395.70±8.89HV 300g , which is lower than the YSZ-C obtained in the example. The cumulative cavitation mass loss after 10 h of the cavitation experiment is 23.8 mg, which is significantly higher than that of the YSZ-C in the example by tens to hundreds of times. Due to the insufficient sintering temperature, even if the carbon source is sufficient, the carbon atoms cannot obtain enough migration energy and therefore cannot be uniformly infiltrated into the YSZ containing more oxygen vacancies. This shows that even if the raw material contains more oxygen vacancies and the carbon source is sufficient, as long as the sintering temperature is not within the required range of the present invention, a carburized ceramic material with good cavitation resistance cannot be obtained.
[0051] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications made without departing from the spirit and principle of the present invention shall be equivalent replacement modes and shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a cavitation-resistant carburized YSZ-C ceramic material, characterized in that: The following steps are involved: 1) Select YSZ powder as the raw material, pour it into a ball mill, add deionized water or anhydrous ethanol 2 to 3 times the mass of YSZ powder into the ball mill as a wet grinding medium, ball mill at 200 to 500 r / min for 20 to 50 hours, and then dry to obtain a powder raw material; 2) pressing the target powder obtained in step 1) into a green body, and then sequentially loading the obtained target green body into a graphite mold in the order of graphite pad-graphite paper-target green body-graphite paper-target green body-graphite paper for hot pressing and sintering, and cooling after sintering to obtain the target product carburized YSZ-C bulk ceramic material; The hot pressing sintering process is divided into the following steps: The first is the heating process: the sample is heated to 800~1100℃ in the furnace at a rate of 10~15℃ / min, and is subjected to a sintering pressure of 10~15MPa. The process lasts for 90~120min in total; the second is the temperature rising and sintering process, the sample is heated to 1200~1450℃ in the furnace at a rate of 5~15℃ / min, and is subjected to a sintering pressure of 20~25MPa. The process lasts for 20~50min in total, and then heated to 1450~1650℃ at a rate of 1~5℃ / min and is subjected to a sintering pressure of 25~30MPa. The process lasts for 90~120min; the last is the self-controlled cooling process, the sample is cooled to 1100~1400℃ at a rate of 5~10℃ / min, and the sintering pressure is changed to 10~15MPa for 10~30min, and then the sintering pressure is changed to 10MPa for 20~50min.
2. A method for preparing a cavitation-resistant carburized YSZ-C ceramic material as claimed in claim 1, characterized in that: In step 1), the purity of the YSZ powder is ≥99% and the particle size ranges from 20 nm to 200 μm.
3. The method for preparing a cavitation-resistant carburized YSZ-C ceramic material according to claim 1, characterized in that: In step 1), the content of yttrium oxide in the YSZ powder is 1 mol% to 10 mol%.
4. The method for preparing a cavitation-resistant carburized YSZ-C ceramic material according to claim 1, characterized in that: In step 1), the wet grinding medium is deionized water or anhydrous ethanol with a purity of 99%.
5. The method for preparing a cavitation-resistant carburized YSZ-C ceramic material according to claim 1, characterized in that: In step 2), the carbon content in the graphite pad and the graphite paper is ≥ 99%.
6. The method for preparing a cavitation-resistant carburized YSZ-C ceramic material according to claim 1, characterized in that: In step 2), the vacuum degree is controlled at 10 -1 Below Pa.
7. A cavitation-resistant carburized YSZ-C ceramic material prepared by the method of claim 1.
Citation Information
Patent Citations
Composite self-lubricating zircite-graphite material
CN1132731A
Process for producing black colored zirconia ceramics with graphite impregnation method and zirconia ceramics thereof
KR1020100137299A
Multi-component ceramic compositions and method of manufacture thereof
US20030008764A1
Yttria-zirconia sintered ceramics for plasma resistant materials
US20240308918A1